China's Soft Power in Indonesia: Eliminating the Remnants of Suharto’s US-Backed Anti-Communist Propaganda - Ahmad Nurcholis (Muslim Politics Review, 2025)
The paper examines the extent to which China's ‘soft power’ in Indonesia is effective in reducing negative perceptions of the anti-communist propaganda launched by the United States-backed Suharto regime during the Cold War. Using theoretical framework proposed by Joseph S. Nye and relevant theories from Joshua Kurlantzick, the study finds that China's soft power performance in Indonesia is significant. After years of harboring a negative image due to anti-communist campaigns, a new, friendlier image of China is emerging. This transformation is reflected by a 2025 Pew Research Center survey, which shows show that 65 percent of Indonesians have a positive perception of China. There are several dimensions of soft power I discuss in this paper, ranging from educational diplomacy such as providing scholarships for Indonesian students; religious diplomacy or ‘Islamic diplomacy’ with through Indonesia’s two largest religious organizations, Nahdlatul Ulama and Muhammadiyah; and the establishment of Confucius Institutes on university campuses. These components were preceded by vigorous economic diplomacy by China, particularly during the Joko Widodo presidency (2014-2024), and were later reinforced by expanding Chinese digital diplomacy, which takes the form of entertainment and gaming platforms for young people, further distancing China from being perceived as a threat. Overall, this demonstrates how China’s soft power efforts have helped to mitigate the lingering negative perceptions of China linked to the Indonesian Communist Party of the mid-twentieth century.